Quadratic equation, Mathematics

If roots of (x-p)(x-q) = c are a and b

what will be the roots of (x-a)(x-b) = -c    please explain?

Ans) (x-p)(x-q)=c


hence,   a+b=p+q

 and      a.b=pq-c


by solving other eq we get


thus        sum of roots=a+b=p+q

       product of roots=a.b+c=p.q

hence its roots are pand q

Posted Date: 3/11/2013 1:47:02 AM | Location : United States

Related Discussions:- Quadratic equation, Assignment Help, Ask Question on Quadratic equation, Get Answer, Expert's Help, Quadratic equation Discussions

Write discussion on Quadratic equation
Your posts are moderated
Related Questions
1. A psychologist developed a test designed to help predict whether production-line workers in a large industry will perform satisfactorily. A test was administered to all new empl

what does the three mean in the power ?

what does algorithm refer to

How many people ca fi in a small cars without seats?

Find the normalized differential equation which has { x, xe^x } as its fundamental set

how do I round a # and decimal

Calculate the value of the following limit. Solution: This first time through we will employ only the properties above to calculate the limit. Firstly we will employ prop